EFFECT OF TEMPERATURE AND 1-METHYLCICLOPROPENE ON THE STORABILITY OF ‘ALEXANDER LUCAS’ PEAR - Balkees, Basem Mahmoud (2021)
The storage life of ‘Alexander Lucas’ pear is limited by the occurrence of internal storage disorders during controlled atmosphere. 1-Methylcyclopropene (1-MCP) can be used to delay pear ripening, however, its interaction with controlled atmosphere (CA) storage conditions is not well understood. ‘Alexander Lucas’ fruit were treated with 1-MCP at 300 nL L-1 for 24 h in air at -0.5 or 1.0 °C before storage. Fruit were kept at -0.5 or 1.0 °C in normal air or CA (2.0 kPa O2 plus <0.7 kPa CO2). After six months storage, superficial scald did not develop. The highest incidence of flesh browning (72.2 %) was scored in air-stored fruit at -0.5 °C without 1-MCP. Storage in air at 1.0 °C plus 300 nL L-1 1-MCP kept 88.8 % of the fruit healthy. In contrast, 1-MCP increased the incidence of flesh and core browning under CA conditions. 1-MCP and CA maintained greener skin color and higher titratable acidity. No significant differences were found in fruit firmness, total soluble solids and ascorbic acid content between the different treatments. In conclusion, the quality of ‘Alexander Lucas’ pear was best maintained during six months storage in normal air at 1.0 °C combined with 300 nL L-1 1-MCP treatment. The storage life of ‘Alexander Lucas’ pear is limited by the occurrence of internal storage disorders during controlled atmosphere (CA). 1-Methylcyclopropene (1-MCP) can be used to delay pear ripening, however, its interaction with CA conditions is not well understood. ‘Alexander Lucas’ fruit were treated with 1-MCP at 300 nL L-1 for 24 h in air at -0.5 or 1.0 °C before being stored. Fruit were kept at -0.5 or 1.0 °C in normal air or CA (2.0 kPa O2 plus <0.7 kPa CO2). After six months of storage, superficial scald did not develop in fruit. The highest incidence of flesh browning (72.2 %) was found in air-stored fruit at -0.5 °C without 1-MCP treatment. Storage in air at 1.0 °C plus 300 nL L-1 1-MCP produced 88.8 % of healthy fruit. In contrast, 1-MCP increased the incidence of flesh and core browning under CA conditions. 1-MCP and CA maintained greener skin color and higher titratable acidity. No significant differences were found for fruit firmness, total soluble solids and ascorbic acid content between the treatments. In conclusion, the quality of ‘Alexander Lucas’ pear was best maintained during six months storage under normal air at 1.0 °C combined with 300 nL L-1 1-MCP treatment.